Exploring the use of student-created multimedia projects as a tool to learning - Yeo, Yvette Soh Guat. (2008)
This study aims to investigate the effectiveness of student-created multimedia project as a tool to learning in the context of the average-ability Primary Six pupils in Singapore. The students’ response in terms of dynamics of cooperative learning and group dynamics would also be discussed.